Baba da Jaka - Kano Dan (Literamed publications, 2009)
The rich man has several fascinating animals in his large compound; he likes to keep them as pets! How old is old Baba Da Jaka, the ugly, lonely stork able to fly and escape Kare, the Dogs vigilant prowl?
Keywords: Tales / Folk / Animals